PENGEMBANGAN MEDIA PAPAN BILANGAN BERBASIS NUMERASI MATERI OPERASI HITUNG PENJUMLAHAN MATEMATIKA SISWA KELAS II UPT SDN KEBONDUREN 01 - Binti Khasanah; Cindya Alfi; Mohamad Fatih (Global Action and Education for Society, 2026)
This research helps grade II students of SDN Kebonduren 01, Blitar Regency, to better understand the addition calculation process, this project intends to create numeracy literacy-based number board media. Through the stages of analysis, design, development, implementation and evaluation, the ADDIE paradigm is applied in research and development (R&D). By using easily available materials and equipped with a rotating number wheel, colorful ornaments, and number cards, the developed media was made interesting and interactive. With validation scores above 87%, the validation results from material, media, and language experts show that this media is very valid and practical to use. Implementation in the classroom showed an increase in students' motivation, understanding, and engagement in learning the material. Positive responses from teachers and students show that this media is effective in supporting basic math learning. Thus, the developed literate numerical analysis-based number board media can be an innovative solution to improve operational analysis learning outcomes in primary schools.